RESPON MAHASISWA TERHADAP BUKU AJAR MORFOLOGI BAHASA ARAB BERBASIS ANALISIS KONTRASTIF - Siti Sulaikho; Lailatul Mathoriyah (DINAMIKA : Jurnal Kajian Pendidikan dan Keislaman, 2019)
Learning Arabic morphology that is not a mother tongue is not an easy matter. Based on the questionnaire given to students, the problem they faced in studying Arabic morphology was that it was difficult to distinguish the terms contained in Arabic morphology by 22.9%, the examples used were always the same in each discussion so as to confuse 14.3%, difficult to find examples other than those already explained by 17.1%, one word can be changed into many other forms by 8.6%, not knowing the meaning of each word change by 14.3%, difficult to translate into Indonesian so it is not easily understood 11.4%, and it is difficult to get an easily understood learning source of 11.4%. This study aims to determine the response of Arabic Language Education study program students at the University of KH. A. Wahab Hasbullah towards Arabic Morphology textbook based on contrastive analysis using quantitative approaches. Student response data collection using a questionnaire instrument. 35 students were conditioned in one room and gave an assessment of the textbooks that had been shown to them. The final results of the 15 assessment points showed that the Arabic Morphology Textbook Based on Contrastive Analysis scored 90.8 with a decent category and a very good predicate.